Facile synthesis of gold trisoctahedral nanocrystals with controllable sizes and dihedral angles. Issue 23 (6th June 2018) - Huo, Da; Ding, Hongming; Zhou, Shan; Li, Jun; Tao, Jing; Ma, Yuqiang; Xia, Younan
Abstract : We demonstrate seed-mediated growth for the facile synthesis of Au trisoctahedral nanocrystals with tunable sizes and dihedral angles. Abstract : Shape-controlled synthesis of Au nanocrystals is of paramount importance to their applications in plasmonics, catalysis, and nanomedicine. While the synthesis of Au nanocrystals enclosed by low-index facets has been greatly advanced over the past two decades, only limited progress has been made for their high-index counterparts. Here we report a robust route to the facile synthesis of Au trisoctahedral nanocrystals enclosed by high-index facets. Unlike the previously reported methods, our synthesis was conducted at room temperature, together with the introduction a new Au(iii ) precursor that was much harder to reduce than AuCl4 – . In the setting of seed-mediated growth, the trisoctahedral nanocrystals could be readily prepared with sizes controllable from 20–80 nm and dihedral angles tunable in the range of 120–180 degrees. We further used computational modeling to demonstrate that the surface-functionalized Au trisoctahedral nanocrystal could outperform its spherical counterpart in terms of endocytic efficacy under identical conditions.